Effect of surface chemistry of Fe-Ni nanoparticles on mechanistic pathways of azo dye degradation - Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Environmental Science & Technology, 2007)
The degradation of Orange G a monoazo dye, in aqueous solutions was investigated using as-synthesized and stored Fe-Ni bimetallic nanoparticles. Batch experiments with a nanocatalyst loading of 3 g/L showed complete. dye degradation (150 mg/L) after 10 min of reactiontime. HPLC-MS analysis of the degradation products showed that assynthesized nanoparticles reductively cleaved the azo linkage to produce aniline as the major degradation product. However, 1-year-stored nanoparticles showed an oxidative degradation of Orange G through a hydroxyl-radical induced coupling of parent and/or product molecules. XPS analysis in corroboration with HPLC-MS data showed that the surface chemistry between Fe and Ni in assynthesized and stored nanoparticles play a crucial role. in directing the mode of degradation. Reductive dye degradation using as-synthesized nanoparticles proceeded through hydride transfer from nickel, whereas formation of a Fe (2+) -Ni(0) galvanic cell in stored nanoparticles generated hydroxyl radicals from water in a nonFenton type reaction. The latter were responsible for the generation of radical centers on the dye molecule, which led to a coupling-mediated oxidative degradation of Orange G. The generation of hydroxyl radicals is further substantiated with radical quenching experiments using ascorbic acid indicating that stored nanoparticles degrade Orange G through a predominantly oxidative mechanism. HPLC-MS and XPS analysis of dye degradation using as-synthesized nanoparticles exposed to air and water confirmed that the reductive or oxidative degradation capability of Fe-Ni nanoparticles is decided by the time and type of catalyst aging process.

Iron-nickel bimetallic nanoparticles for reductive degradation of azo dye orange G in aqueous solution - Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Applied Catalysis B-Environmental, 2008)
The degradation of Orange G, a monoazo dye, in aqueous solutions was investigated using Fe-Ni bimetallic nanoparticles. Transmission electron microscopy (TEM) of as-synthesized nanoparticles showed the presence of spherical particles having a size of 20-40 nm. X-ray photoelectron spectroscopy (XPS) did not detect the presence of nickel on the nanoparticle surface, which suggested a uniform distribution of both metals inside the particle core. Batch experiments with a minimum nanocatalyst loading of 3 g/L showed complete dye degradation after 10 min of reaction time. The degradation efficiency was linearly dependent on the initial dye concentration, pH of the solution and total Fe-Ni catalyst concentration. The efficiency increased with increasing Fe-Ni concentration and decreasing pH of the solution, but decreased with an increase in the dye concentration. The degradation rate followed first order reaction kinetics with respect to the dye concentration. High performance liquid chromatography-mass spectrometry (HPLC-MS) analysis of the degradation products revealed that the degradation mechanism proceeds through a reductive cleavage of the azo linkage resulting in the formation of aniline and surface-adsorbed naphthol amine derivatives. The latter are subsequently hydroxylated through an oxidative process. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Azo Dye; Degradation; iron; Nanoparticles; Nickel

Reductive dechlorination of gamma-hexachlorocyclohexane using Fe-Pd bimetallic nanoparticles - Nagpal, Varima; Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Journal of Hazardous Materials, 2010)
Nanoscale Fe-Pd bimetallic particles were synthesized and used for degradation of lindane (gamma-hexachlorocyclohexane) in aqueous solution. Batch studies showed that 5 mg/Lof lindane was completely dechlorinated within 5 min at a catalyst loading of 0.5 g/L and the degradation process followed first-order kinetics. GC-MS analysis in corroboration with GC-ECD results showed the presence of cyclohexane as the final degradation product. The proposed mechanism for the reductive dechlorination of lindane involves Fe corrosion-induced hydrogen atom transfer from the Pd Surface. The enhanced degradation efficiency of Fe-Pd nanoparticles is attributed to: (1) high specific surface area of the nanoscale metal particles (60 m(2)/g), manyfold greater that of commercial grade micro- or milli-scale iron particles (similar to 1.6 m(2)/g); and, (2) increased catalytic reactivity due to the presence of I'd on the Surface. Recycling and column studies showed that these nanoparticles exhibit efficient and sustained catalytic activity. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bimetallic; Cyclohexane; Degradation; kinetics; Lindane; Nanoparticles

Perspectives for nano-biotechnology enabled protection and nutrition of plants - Ghormade, Vandana; Deshpande, Mukund V.; Paknikar, Kishore M. (Biotechnology Advances, 2011)
Indiscriminate use of pesticides and fertilizers causes environmental pollution, emergence of agricultural pests and pathogens, and loss of biodiversity. Nanotechnology, by virtue of nanomaterial related properties, has potential agro-biotechnological applications for alleviation of these problems. The literature pertaining to the role of nanotechnology in plant and soil systems demonstrates that nanomaterials may assist in a) the controlled release of agrochemicals for nutrition and protection against pests and pathogens, b) delivery of genetic material, c) sensitive detection of plant disease and pollutants and d) protection and formation of soil structure. For instance, porous silica (15 nm) and biodegradable, polymeric chitosan (78 nm) nanoparticles displayed slow release of encapsulated pesticide and fertilizer, respectively. Further, nanosized gold (5-25 nm) delivered DNA to plant cells while iron oxide (30 nm) based nanosensors detected pesticides at minute levels. These functions assist the development of precision farming by minimizing pollution and maximizing the value of farming practice. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Biofertilizer; Biopesticides; Controlled delivery; Fertilizer; Genetic material; Nanomaterials; Nanosensors; Pathogen; Pesticides; Residues

Reply to comment on ``Reductive dechlorination of gamma-hexachlorocyclohexane using Fe-Pd bimetallic nanoparticles'', by C. Noubactep - Nagpal, Varima; Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Journal of Hazardous Materials, 2012)

Hyperthermia and doxorubicin release by Fol-LSMO nanoparticles induce apoptosis and autophagy in breast cancer cells - Kulkarni-Dwivedi, Neha; Patel, Pratikshkumar R.; Shravage, V. Bhupendra; Umrani, Rinku D.; Paknikar, Kishore M.; Jadhav, Sachin H. (Nanomedicine, 2022)
Background: Studies on the anticancer effects of lanthanum strontium manganese oxide (LSMO) nanoparticles (NPs)-mediated hyperthermia at cellular and molecular levels are scarce. Materials & methods: LSMO NPs conjugated with folic acid (Fol-LSMO NPs) were synthesized, followed by doxorubicin-loading (DoxFol-LSMO NPs), and their effects on breast cancer cells were investigated. Results: Hyperthermia (45 degrees C) and combination treatments exhibited the highest (similar to 95%) anticancer activity with increased oxidative stress. The involvement of intrinsic mitochondria-mediated apoptotic pathway and induction of autophagy was noted. Cellular and molecular evidence confirmed the crosstalk between apoptosis and autophagy, involving Beclin1, Bcl2 and Caspase-3 genes with free reactive oxygen species presence. Conclusion: The study confirmed hyperthermia and doxorubicin release by Fol-LSMO NPs induces apoptosis and autophagy in breast cancer cells.
Keywords: Apoptosis; Autophagy; Breast cancer; combination therapy; doxorubicin; Folic acid; hyperthermia; LSMO; MDA-MB231 cells; PEG